FACTORS AFFECTING WORK FATIGUE IN INPATIENTS' FEMALE NURSES: LITERATURE REVIEW - Rosnia, Shafiera; Utari, Dyah; Agustina (Journal of Public Health Research and Community Health Development, 2023)
ABSTRACT Background: Work fatigue is a decreasing condition of human body physically and mentally which can cause errors and work accident  that affect performances and productivities. In several developed countries  around 25% of all female workers, including nurses, experience work fatigue. Purpose: To determine whether there are relationships between sleep patterns, work shifts, workload, and occupational stress with work fatigue in female nurses inpatient room. Method:  This is a review study of literature published between 2010 – 2020 available from Google Scholar and PubMed. Result: This study contained 20 previous research journals and found that 11 journals proved a strong relationship between sleep patterns and work fatigue, 5 journals proved there were a relationship between workload and work fatigue, 7 journals proved there were a relationship between work shifts and work fatigue, and 5 journals proved there were a relationship between occupational stress and work fatigue. Conclusion: The analysis state that sleep patterns most related to work fatigue in nurses. Suggestion: Promotion of occupational and safety at the work place is needed to improve the occupational health of nurses, provide a comfortable work space, make recreational activities, and provide balanced nutritional food.